Two Routes for Activation in the Priming of Categorical Coordinates. - Ray, Suchismita; Bly, Benjamin Martin (Journal of General Psychology, 2008)
The authors Operationalized category priming us participants' recognition facilitation of nonstudied, low semantically similar exemplars by studied exemplars in a category. The existing literature either does not examine the effect of studied exemplars on nonstudied exemplars in a category or fails to show an appreciable amount of category priming. In 2 experiments, the authors demonstrated a unique process to account for the category priming effect and distinguish it from the semantic priming effect, facilitation of semantically similar exemplars, in the context of a category. In Experiment 1 A, the authors used a multidimensional sealing technique to examine participants' internal structure of different categories. In Experiment 1B, the authors used a lexical decision task that used these internal structures to show that semantic encoding of category exemplars causes activation of existing category knowledge in memory. Consequently, participants easily recognized nonstudied, low semantically similar exemplars in a category. However, recognition facilitation between high semantically similar exemplars did not require category knowledge activation. Reprinted by permission of the publisher.